The Impact of Understanding Microinsurance and Risk Mitigation on the Business Resilience of Microinsurance Participating MSMEs - Nova Fitri Yasdiana; Andri Soemitra; Isnaini Harahap (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of microinsurance understanding and risk mitigation on the business resilience of microinsurance participating MSMEs in Medan's Central Market Center. This research uses a quantitative method with the SEM-PLS approach through the SmartPLS 4 application, with a sample of 95 respondents selected using a purposive sampling technique. The results of the data analysis indicate that the Microinsurance Understanding variable has a positive and significant influence on MSME business resilience (t = 3.379; p = 0.001). In contrast, the Risk Mitigation variable does not show a significant influence on MSME business resilience (t = 0.367; p = 0.714). This is influenced by the very high conceptual overlap in the eyes of respondents between the two independent variables (HTMT = 0.982), where business actors consider concrete risk mitigation actions to be inherent in the microinsurance instrument itself. Simultaneously, this model is able to explain the variance in MSME business resilience by 37.2% (R^2 = 0.372). These findings indicate that deepening insurance literacy is a crucial key to increasing the financial resilience of business actors in the face of economic uncertainty.